Coal Prices and Foreign Ownership on the Capital Structure of Indonesian Coal Companies - Pratiwi, Hanum Amalia Budhi; Achsani, Noer Azam; Irawan, Toni (Jurnal Keuangan dan Perbankan, 2022)
This paper investigated the effect of coal prices and foreign ownership on the capital structure of coal companies in the Indonesian stock exchange. This study used debt to equity ratio (DER) to proxy capital structure and control variables, i.e., size, liquidity, and profitability. This study employed the statistic descriptive analysis and regression analysis of panel data and covered quarter data of 23 coal companies listed in the Indonesian stock exchange in a 3-year time horizon (2018-2020). This study concludes that ten out of 23 coal companies have more than 100% DER. Based on the sources of liabilities, debt originating from third parties is the primary source of debt for coal companies listed on the IDX in 2018-2020. The next order of sources of debt in a row is bank loans, debts from related parties, lease payables, bonds, and dividends. The result showed that ten out of 23 companies have a more than 100% capital structure value. The panel data regression analysis showed that capital structure significantly impacts coal prices, foreign ownership, size, liquidity, and profitability. As one of the main coal exporters, Indonesia has a good bargaining position in the international market. An investor can use the movement of coal prices as one of the criteria for deciding to invest in this industry.